ANALISIS MANAJEMEN DINASTI DALAM PENGELOLAAN PONDOK PESANTREN DALAM PENYALAHGUNAAN ASET WAKAF DALAM PENYALAHGUNAAN ASET WAKAF PONDOK XXXXX DALAM MENGHADAPI ERA DIGITAL - Pranata, Mohammad Firlie; Zakki, Nurdody (Aktiva : Jurnal Akuntansi dan Investasi, 2023)
Islamic Boarding Schools in managing their waqf for the benefit of the ummah and blessings for their managers. The 2006 National Committee on Governance Policy (KNKG) guidelines explain that every company must ensure that the principles of Good Corporate Governance (GCG) are applied to every aspect of business and at all levels of the company. This article aims to find out about Dynasty Management in the Management of Islamic Boarding Schools in the Misuse of XXXXX Pondok Waqf Assets in facing the Digital Age. The results of the study show that Dynasty Management is very influential and has a major impact on asset misuse, so the need for GCG principles, namely transparency, accountability, responsibility, independence and fairness, is known to improve the land management reporting control system online or digitally as a tool needed by the Executor of Maintenance and Expansion of Waqf Land (P3TW).